2020
DOI: 10.1021/acssensors.0c00507
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Microfluidic Devices for Enhanced Online Sampling and Direct Optical Measurements

Abstract: 3D printing has emerged as a robust technique to fabricate reliable and reproducible microfluidic devices. However, a limitation of 3D-printed devices has been the low transparency even when printed in a "clear" material. There are currently no reports regarding direct optical measurements through a 3D-printed device. Here, we present for the first time that the printing orientation can affect the transparency of a 3D-printed object. With the optimal orientation, we printed a microfluidic detector that was suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…As for this work a 3D-inkjet printer is used, which has a print head with a predefined trajectory. Therefore, it was also important to investigate the influence of the CAD-model orientation on the optical properties and consequently how parts should be placed on the plate [14]. Since deflection prisms have flat surfaces, one solution is to bond cover glasses to improve the reflective properties of the hypotenuse.…”
Section: Introductionmentioning
confidence: 99%
“…As for this work a 3D-inkjet printer is used, which has a print head with a predefined trajectory. Therefore, it was also important to investigate the influence of the CAD-model orientation on the optical properties and consequently how parts should be placed on the plate [14]. Since deflection prisms have flat surfaces, one solution is to bond cover glasses to improve the reflective properties of the hypotenuse.…”
Section: Introductionmentioning
confidence: 99%
“…However, our recent work has demonstrated a new method to optimize the transparency during printing. 68 Using a Projet MJP 5600 printer and VisiJet CR-CL 200 material, we demonstrated that by optimizing the printing orientation, the transparency of a part could be tuned. 68 Our results were based on the hypothesis that due to the stacking of the layers in the z -direction during printing as demonstrated in Fig.…”
Section: Part I: Common 3d-printing Technologies To Develop Microflui...mentioning
confidence: 95%
“…68 Using a Projet MJP 5600 printer and VisiJet CR-CL 200 material, we demonstrated that by optimizing the printing orientation, the transparency of a part could be tuned. 68 Our results were based on the hypothesis that due to the stacking of the layers in the z -direction during printing as demonstrated in Fig. 7D, the sides of the part are rougher and less transparent.…”
Section: Part I: Common 3d-printing Technologies To Develop Microflui...mentioning
confidence: 95%
See 2 more Smart Citations